Infliximab is associated with an increased risk of serious infection in patients with psoriasis in the U.K. and Republic of Ireland: results from the British Association of Dermatologists Biologic Interventions Register (BADBIR). (21st October 2018) - Yiu, Z.Z.N.; Ashcroft, D.M.; Evans, I.; McElhone, K.; Lunt, M.; Smith, C.H.; Walton, S.; Murphy, R.; Reynolds, N.J.; Ormerod, A.D.; Griffiths, C.E.M.; Warren, R.B.; et al.
Summary: Background: Patients with psoriasis and clinicians are concerned that infliximab may be associated with a risk of serious infections. Objectives: To compare the risk of serious infections associated with infliximab in patients with chronic plaque psoriasis against a cohort on nonbiologic systemic therapies. Methods: A prospective cohort study was performed using data from the British Association of Dermatologists Biologic Interventions Register (BADBIR). Infliximab was compared with nonbiologic systemic therapies, inclusive of any exposure to methotrexate, ciclosporin, acitretin, fumaric acid esters, psoralen‐ultraviolet A or hydroxycarbamide. Serious infections were those associated with hospitalization, the use of intravenous antimicrobial therapy and/or those that led to death. Propensity score inverse probability treatment weights were used to adjust for potential confounding from a priori identified covariates. Cox proportional hazards models were calculated to obtain hazard ratios (HRs). Results: In total, 3843 participants were included for analysis up to October 2016. The incidence rates were significantly higher in the infliximab cohort (47·8 per 1000 person‐years) [95% confidence interval (CI) 35·7–64·0], compared with 14·2 per 1000 person‐years (95% CI 11·5–17·4) in the nonbiologic systemic cohort. Infliximab was associated with an overall increase in the risk of serious infection compared with nonbiologics [adjusted HR (adjHR) 1·95, 95% CI 1·01–3·75] and methotrexate only (adjHR 2·96, 95% CI 1·58–5·57) and a higher risk of serious infection in the first 6 months of therapy (adjHR 3·49, 95% CI 1·14–10·70). Conclusions: Infliximab is associated with an increased risk of serious infections compared with nonbiologic systemic therapies in patients with psoriasis in the U.K. and the Republic of Ireland. Abstract : What's already known about this topic? Randomized clinical trials are not sufficiently powered to investigate the risk of serious infection in patients with psoriasis who are undergoing treatment with infliximab. Published observational studies have used different methods to adjust for confounding and different comparators. Previous studies also lacked the adequate sample size to obtain a precise estimate of the risk of serious infection for infliximab. What does this study add? Using methods that better address bias and confounding, our study suggests that infliximab is associated with a higher risk of serious infections compared with nonbiologic systemic therapies in patients with psoriasis. Patients should be counselled on the risk of serious infection before infliximab is prescribed. Linked Comment: Puig. Br J Dermatol 2019;180 : 257–258 . Plain language summary available online Respond to this article